Extracellular Synthesis, Characterization and Antibacterial Activity of Silver Nanoparticles by a Potent Isolate Streptomyces sp. DW102 - Sheik, Gouse Basha; Raheim, Ali Ismail Ali Abdel; Alzeyadi, Zeyad Abdullah; AlGhonaim, Mohammed Ibrahim (Asian Journal of Biological and Life Sciences, 2019)
The global problem of antibiotic resistance and the lack of novel antibiotics in the markets is soon to be a health care crisis. Silver nanoparticles are recently considered as a tool of the medical field, especially in therapeutic applications.Streptomyces sp. is a natural antibiotic producer and could be utilized for the production of nanoparticles enhanced antibiotics. In the present investigation, 17 actinomycetes were isolated from soil samples collected from various regions in Dawadmi governorate, Riyadh province. Isolate DW102 was identified as potent isolate based on the ability to synthesize silver nanoparticles along with broad spectrum antibacterial activity when compared with other isolates. The potent isolate DW102 was identified asStreptomycessp. Biosynthesized AgNPs were characterized by UV-Vis Spectroscopy, Scanning Electron Microscopy (SEM) and Energy Dispersive X-ray analysis (EDX). Bioynthesized Ag-NPs showed antimicrobial activity against Multi Drug Resistant (MDR) strains ofStaphylococcus aureus, Enterococcus faecalis, Escherichia coliandKlebsiella pneumonia.The combination of antibiotics with AgNPs showed an overall percentage increase in average fold-area of zone of inhibition (ZOI) in this study.
Keywords: Antibacterial activity; Multi Drug Resistant; Silver nanoparticles; Streptomyces sp.; Zone of inhibition